Have a Break, Have a ... National Currency: When Do Monetary Unions Fall Apart? - Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2004)
Historically, dissolutions of currency unions are not unusual. I use an annual panel data set covering 245 country pairs that use a common currency (of which 128 are dissolved) from 1948 through 1997 to characterize currency union exits. I find that departures from a currency union tend to occur when there is a large inflation differential between member countries, when the currency union involves a country which is closed to international trade and trade flows dry up, and when there is a change in the political status of a member. In general, however, macroeconomic factors have only little predictive power for currency union dissolutions.
Keywords: 330; monetary union; sovereign currency; dissolution; exit